Renal safety in 3264 HCV patients treated with DAA-based regimens: Results from a large Italian real-life study. Issue 2 (February 2020) - D'Ambrosio, Roberta; Pasulo, Luisa; Giorgini, Alessia; Spinetti, Angiola; Messina, Emanuela; Fanetti, Ilaria; Puoti, Massimo; Aghemo, Alessio; Viganò, Paolo; Vinci, Maria; Menzaghi, Barbara; Lombardi, Andrea; et al.
Abstract: Background: Sofosbuvir (SOF)-based regimens have been associated with renal function worsening in HCV patients with estimated glomerular filtration rate (eGFR) ≤ 45 ml/min, but further investigations are lacking. Aim: To assess renal safety in a large cohort of DAA-treated HCV patients with any chronic kidney disease (CKD). Methods: All HCV patients treated with DAA in Lombardy (December 2014–November 2017) with available kidney function tests during and off-treatment were included. Results: Among 3264 patients [65% males, 67% cirrhotics, eGFR 88 (9–264) ml/min], CKD stage was 3 in 9.5% and 4/5 in 0.7%. 79% and 73% patients received SOF and RBV, respectively. During DAA, eGFR declined in CKD-1 (p < 0.0001) and CKD-2 (p = 0.0002) patients, with corresponding rates of CKD stage reduction of 25% and 8%. Conversely, eGFR improved in lower CKD stages (p < 0.0001 in CKD-3a, p = 0.0007 in CKD-3b, p = 0.024 in CKD-4/5), with 33–45% rates of CKD improvement. Changes in eGFR and CKD distribution persisted at SVR. Baseline independent predictors of CKD worsening at EOT and SVR were age (p < 0.0001), higher baseline CKD stages (p < 0.0001) and AH (p = 0.010 and p < 0.0001, respectively). Conclusions: During DAA, eGFR significantly declined in patients with preserved renal function and improved in those with lower CKD stages, without reverting upon drug discontinuation.